Prognostic biomarker RIMS1 and its association with immune infiltration in glioblastoma - Erxing Tao; Qimin Song; Jialin Tang; Wenqiang Xin; Zhipeng Xiao; Zhixin Liu; Guangbin Xie (Scientific Reports)
Abstract Glioblastoma (GBM) is the most common and deadly malignant tumor of the nervous system. RIMS1, a member of the RAS gene superfamily, plays a critical role in signaling pathways regulating cell growth and differentiation. However, the prognostic value of RIMS1, particularly its relationship with immune cell infiltration in gliomas, has not been fully explored. RIMS1 expression in glioblastoma cells and tissues was assessed using bioinformatics platforms. The association between RIMS1 expression levels and overall survival was analyzed using Kaplan-Meier analysis and Cox regression model. To evaluate the proliferative and migratory capacity of GBM cells, we conducted CCK-8, colony formation, transwell, and scratch assays. With data from The Cancer Genome Atlas (TCGA), we investigated the correlation between RIMS1 expression and immune cell infiltration levels and assessed the prognostic impact of RIMS1 on GBM patient survival, focusing on its potential involvement in immune pathways. Lower RIMS1 expression was associated with poorer overall survival and was linked to patient age, gender, and tumor grade. Importantly, RIMS1 expression showed a significant correlation with immune cell infiltration levels, suggesting that RIMS1 influences glioblastoma survival, at least in part, through immune-related mechanisms. In glioblastoma patients, elevated RIMS1 expression may serve as an independent prognostic biomarker, potentially through its impact on immune cell infiltration.